The Effectiveness of Employing Role-Playing Techniques to Enhance Reading Skills in Elementary School Students - Hartono Hartono (Indonesian Journal of Innovative Teaching and Learning, 2024)
The reading ability of primary school students is still low, and there are still many elementary school students who are not fluent in speed reading. Therefore, teachers are expected to overcome the problems that occur in students. The purpose of this study was to determine the effectiveness of the role-playing method as a medium to improve students' reading skills. The research method used pre-experiment research with a pretest-posttest design. This research was conducted at SD Muhammadiyah Wonokromo 1 in the 2022 academic year. The research sample was 25 students. Data collection using a reading ability scale. Data analysis using statistical analysis (t-test). The results showed the sig value = 0.000, which means it is smaller than α 0.05 (Ho: rejected and Ha: accepted). The results of the study concluded that the role-playing method can effectively be used as a medium to improve the reading skills of elementary school students. The results of this study contribute as a novelty and study material both theoretically and practically regarding the effectiveness of the role-playing method as a medium to improve the reading skills of elementary school students.